A Retrospective Assessment of Syphilis Seroprevalence among Pregnant Women, Cape Coast, Ghana - Tetteh, Ato Kwamena; Arthur, Sadick; Bram, Prince; Baffe, Charles; Aglagoh, Godsway; Tetteh, Gifty Rhodalyn; Agyarko, Edward (Journal of Diseases, 2019)
This is a hospital-based cohort study, which aimed at assessing the seroprevalence of syphilis among pregnant women who sought antenatal care at the Cape Coast Metropolitan Hospital (CCMH). We retrospectively analyzed secondary data of 2,640 term pregnant women, who gave birth from January, 2016 to December, 2018. Data was compiled from the CCMH delivery register. Out of the 2,640 pregnant women who delivered from 2016 through 2018, 107 [4.1%, 95% CI: 3.3 – 4.8] tested reactive (2016, 1.5%, 40/2640; 2017, 1.0%, 26/2640; 2018, 1.6%, 41/2640). Seroprevalence among the primagravida (those with first pregnancy) was 0.8%, while that among the multigravida (≥ 2 pregnancies) was 3.3% (χ2 = 37.562, p = 0.021). Pregnant women within the age group of 22-31 years were the most reactive, 2.3% (60/2640), followed by 32-41 years, 1.1% (30/2640). A prevalence of 1.9% (50/2640) was recorded among Junior High School holders, while 0.2% (5/2640) was found among those who have attained tertiary level education. A Relatively high prevalence of 3.0% (78/2640) was recorded among informal workers compared to the unemployed, 0.9% (23/2640). An appreciable proportion of 18.9% (499/2640) had no syphilis testing record indicated in the register. Early detection of syphilis and treatment of infected partners, rapid testing for ANC non-attendants at the maternity/obstetrics and gynecology departments is highly recommended either before or after delivery, as laboratory services may not be available in the nights when most deliveries occur.